Genetic Fine‐Mapping of a Quantitative Trait Locus (QTL) Associated with Embryogenic Tissue Culture Response and Plant Regeneration Ability in Maize (Zea mays L.). Issue 2 (1st July 2018) - Salvo, Stella; Cook, Jason; Carlson, Alvar R.; Hirsch, Candice N.; Kaeppler, Shawn M.; Kaeppler, Heidi F.
Abstract : Embryogenic and regenerable tissue cultures are widely utilized in plant transformation, clonal propagation, and biological research applications. Germplasm utilized in those applications are limited, however, due to genotype‐dependent culture response. The goal of this study was to identify genomic regions controlling embryogenic and regenerable tissue culture response in the globally important crop, maize ( Zea mays L.), toward the long‐term objective of developing approaches for genotype‐independent plant genetic engineering and clonal propagation systems. An inbred maize line, WCIC2, nearly‐isogenic to reference inbred B73, was developed by phenotypic selection and molecular marker analysis. WCIC2 has over 50x increase in tissue culture response relative to the recurrent parent, B73. This line was used to genetically fine‐map a region on chromosome 3 controlling embryogenic and regenerable tissue culture response to a 23.9 Mb region. WCIC2 and derivatives will be useful materials to enable maize research in a genetic background similar to B73, and our genetic mapping results will advance research to identify causal genes controlling somatic embryo formation and plant regeneration in maize.